2016
DOI: 10.1089/thy.2016.0108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Patients with Autoimmune Thyroid Disease: A Meta-Analysis

Abstract: About 1/62 patients with ATD have biopsy-verified CD. It is argued that patients with ATD should be screened for CD, given this increased prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 74 publications
(124 reference statements)
1
45
1
2
Order By: Relevance
“…The high prevalence of CD among patients with type 1 diabetes mellitus (up to 13.5%) is probably due to clinical and pathogenic overlap [68], and symptoms are often modest or absent. The results partially represented in Table 3 and found in meta-analyses [69, 70] of high CD prevalence in children with Down syndrome (more than 5%) and autoimmune thyroid disorders (about 6%) should motivate screening for CD in these cohorts. CD is also common in patients who have a first- and second-degree kinship with persons with CD, at 10 and 2.6%, respectively [71-73].…”
Section: Screening Strategies In Paediatric Populationsmentioning
confidence: 99%
“…The high prevalence of CD among patients with type 1 diabetes mellitus (up to 13.5%) is probably due to clinical and pathogenic overlap [68], and symptoms are often modest or absent. The results partially represented in Table 3 and found in meta-analyses [69, 70] of high CD prevalence in children with Down syndrome (more than 5%) and autoimmune thyroid disorders (about 6%) should motivate screening for CD in these cohorts. CD is also common in patients who have a first- and second-degree kinship with persons with CD, at 10 and 2.6%, respectively [71-73].…”
Section: Screening Strategies In Paediatric Populationsmentioning
confidence: 99%
“…Autoimmune thyroiditis is the most prevalent coexisting autoimmune disorder in patients with celiac disease [9]. A pooled analysis, including 6024 patients with autoimmune thyroiditis, found a markedly increased prevalence of biopsy-confirmed coeliac disease, allowing the authors to conclude that all patients with autoimmune thyroiditis should be screened for the presence of coeliac disease [10]. The association between autoimmune thyroid disease and coeliac disease may be explained by low selenium [11] or vitamin D [12] status secondary to their malabsorption, the interaction of tissue transglutaminase-2 IgA antibodies to thyroid follicles and thyroid extracellular matrix [13], or by a shared immunogenetic make-up [14].…”
Section: Article Thiemementioning
confidence: 99%
“…Although the prevalence of CD in those diseases varied substantially among studies, a systematic review with meta-analysis showed that 6 % of patients with type 1 diabetes have biopsy-confirmed celiac disease [ 11 ]. In autoimmune thyroid disease, a pooled analysis with 6024 patients found a prevalence of biopsy-verified CD of 1.6 %, and the prevalence of CD was higher in children with autoimmune thyroid disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%